Shelf life extension of ambient-stored banana cake using banana powder - Samsudin, N. I. P.; Roslan, N. A.; Mahmud @ Ab Rashid, Nor Khaizura; Hasan, Hanan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Maintaining the quality of bakery products is vital for consumers’ health and preference. Since bakery products are intermediate-moisture foods, spoilage by moulds is among the major causes of shelf life reduction. In the present work, the effects of substituting banana purée with banana powder to extend the shelf life of banana cakes were investigated over a ten-day storage period. Three types of banana cake were made using banana purée (control), laboratory-formulated powder (LP), and commercial powder (CP). Results indicated a significant difference in moisture contents and water activities between all treatments in which LP and CP exhibited mould growth at day 9 compared to day 5 in control. For fungal load, LP yielded the lowest CFU by the end of storage period. Although significant differences in texture and appearance were noted between all treatments, untrained sensory panellists scored LP as acceptable. Further works are therefore warranted to assess LP’s commercialisation potentials.